Manifest destiny 2.0 genre trouble in game worlds - Humphreys, Sara, 1968- (Postwestern horizons., 2021)
Examining the social and cultural implications of noir and Western narratives in video games, Manifest Destiny 2.0 explores the performative literacy of gaming as a means by which Western and noir genres continue to influence twenty-first-century attitudes and global culture.